Redes de cooperação e desenvolvimento do turismo local: um estudo de caso no circuito italiano de turismo rural – Município de Colombo-PR - Czajkowski, Adriana (2009)
Tourism is a typical phenomenon of modernity, with significant potential, capable of stimulating benefits and sustainable development of a place. Thus, cooperation networks have become an important alternative for the tourism development, improving profits and collective benefits to social actors inserted on tourism clusters. It is important to foment the social actors involvement for a joint work as the best way to identify and make good use of the tourist region opportunities. For this reason, this study analyzes how the cooperation network among social actors of “Circuito Italiano de Turismo Rural” has contributed to the tourism development in the municipal district of Colombo-PR. The analysis focus choice was based on Michael Porter’s Clusters Theory and Diamond of National Advantage. The methodology used was a qualitative research, classified as exploratory-descriptive, considering the case study as procedure method. The data were obtained through semi-structured interviews with 10 social actors of “Circuito Italiano de Turismo Rural”. The data analysis was based on document and content analysis, relating to the theoretical framework. The study outcomes suggest that the cooperation network among the social actors of “Circuito Italiano de Turismo Rural” has contributed to the tourism development in the municipal district of Colombo-PR.